Tourist Attractiveness of Protected Areas in the Podlaskie Province in the Opinion of its Residents - Pietrzak-Zawadka Joanna; Zawadka Jan (Studia Ekonomiczne i Regionalne, 2018)
Subject and purpose of work: The article explores the issue of protected areas in the Podlaskie Province with particular reference to Natura 2000 areas. Its purpose is to investigate the familiarity of those areas as well as the perception of their attractiveness among the inhabitants of the Podlaskie Province.